Diversidad de especies arvences en plantaciones de tectona grandis L.F.(TECA) de 4 años a 15 años de edad en la época lluviosa de los cantones de Pichincha, Palenque y Balzar, año 2019 - Burgos Cevallos, José Antonio (2020)
The objective of the research is to identify the diversity of weed species in plantations of Tectona Grandis L.f. (teak), from 4 to 15 years of age in the rainy season of the cantons of Pichincha, Palenque and Balzar, year 2019, where a total of 59 was found. species in the 24 Sampling Units in the six study sites. Qualitative and quantitative data were taken such as common name, description of the individual, number of individuals per species and the coordinates of each site, for the diversity analysis parameters were taken: frequency, abundance, the Jacard, Shannon indexes were also used and Simpson, in addition to the cluster analysis that measured the interactions between the different sampling units. We found 5336 individuals in 59 species, of which the most abundant was: Momordica charantia, were grouped into 34 families and 51 genera. The Shannon Index determined high diversity at five sites of study and average diversity at one site, while the Simpson Index determined an average diversity for all sampling units